Factors influencing successful halal logistics practices among Japanese logisitcs companies / Nur Izzaty Mohamad Dalian - Mohamad Dalian, Nur Izzaty (2023)
The increasing number of Muslim population around the world has influenced the growth of halal business market and resulted in its increasing demand. This has affected the logistics service providers and prompted the Japanese halal logistics companies to take this opportunity to be certified as halal logistics service providers. Studies which provide evidence of the factors influencing successful halal logistics among Japanese logistics companies are still scarce. Therefore, this study aims to identify the sustainability of halal logistics businesses after getting the halal certification. Three objectives were established. The first objective is to identify the extent of the involvement of Japanese companies in halal-related businesses. Four themes which derived from the literature review and preliminary study were proposed in the theoretical framework. The themes are culture, internationalisation, management support, and government support. The second objective is to identify the extent of halal logistics practices among the Japanese logistics companies. Qualitative approach was employed and three halal Japanese logistics companies with six respondents contributed to the findings. Finally, the final objective is to develop a framework of successful halal logistics practices among Japanese logistics companies. The final objective was achieved by identifying three themes, namely culture, seek support, and integrity in the successful halal logistics practices by the Japanese logistics companies. This study has succeeded in showing evidence of the sustainability of Japanese logistics companies in halal businesses after getting the halal certification. This study has also provided insights into the reality of halal logistics businesses so that any halal industry player could learn from it.